Pengolahan Pupuk Cair Bakteri Fotosintetik yang Diaplikasikan pada Tanaman Sayuran di Desa Belayung Baru Kabupaten Banjar - Abdillah, Muhammad Helmy; Rahmawati, Linda; Lukmana, Mila; Iswahyudi, Herry; Indriani, Indriani; Budi, Ismed Setya; Mariana, Mariana (Alamtana: Jurnal Pengabdian Masyarakat UNW Mataram, 2023)
Vegetable plants on marginal land typologies require increased nutritional intake from organic and inorganic materials to enhance their growth. In addition, the enrichment of mutualistic microbial diversity plays a significant role in the absorption of these nutrients. However, not all cultivators know how to increase land productivity and crop yields; therefore, the activity of processing liquid fertiliser containing photosynthetic bacteria was held with the aim of training the residents of Belayung Baru Village in making liquid fertiliser from photosynthetic bacteria, so that it is hoped that it can change the behaviour of residents in applying organic materials in a correct and appropriate way. The method used in this activity was outreach containing socialisation and demonstrations, which were carried out on October 22, 2023, involving 33 residents of Belayung Baru Village, supported by an implementation team consisting of 7 lecturers and 5 students. This activity resulted in increased knowledge and skills of the assisted subjects regarding the processing of liquid organic fertiliser containing photosynthetic bacteria and its impact when applied to plants.